Risk factors for surgical site infections after caesarean section at Yaounde, Cameroon - Tebeu, Pierre M.; Kamdem, Aurelien; Ngou-Mve-Ngou, Jean P.; Meka, Esther; Antaon, Jesse S. S.; Loic, Meukem Tegue; Fouedjio, Jeanne (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Surgical site infection is the invasion by microorganisms of the tissue layers affected by the surgical procedure. Maternal morbidity from infections has been shown to be higher after caesarean section compared to the vaginal delivery. Objective of the research was to analyze the risk factors associated with surgical site infections after caesarean section. Methods: This was a cross sectional (affected/non affected) study approved by the institutional committee for ethics and research of the faculty of medicine and biomedical sciences. A total of 310 medical files were assessed, 62 files from patients with surgical site infections and 248 files from patients without any complications. The data was collected using a pretested questionnaire and analyzed using the statistical package for the social sciences (SPSS) software version 22.0. The Chi squared and the Fisher exact tests were used to assess homogeneity between the 2 groups. Odd ratio 95% confidence interval was used to assess the association between the variables. Results: The proportion of surgical site infections during the study was 1.81%. Factors associated with surgical site infections were premature rupture of membranes (OR: 2.065; 95% CI 1.051-4.05; p=0.035); the vertical midline incision (OR=5.26; 95% CI; 1.41-19.57; p=0.013) and a operation by a resident physician doctor (OR=1.98; 95% CI 1.09-3.59; p=0.02). Conclusions: A factors associated with surgical site infections after caesarean section are a premature rupture of membranes, vertical midline incision and the qualification of the practitioner.